PENGGUNAAN KATA PISUHAN BERDASARKAN GENDER (Penggunaan Kata Pisuhan Berdasarkan Gender Pada Mahasiswa Fakultas Bahasa dan Seni Universitas Negeri Surabaya) Intan Puspita Sari, Siti Lutfia, Afif Hanafi dan Endang (Lentera, Jurnal Studi Perempuan, 2010)
Abstract Language is man communication means so that man cannot get out of language. Language variety in man interaction all kinds. Language variety is applied to lay open flavor like, proud, marveled, hated, sorrowful, disappointed, sulked, despised, etcetera. Man expression in the soulful passed language all kinds, one of them through pisuhan. Words pisuhan often applied by children, adolescent, as well as adult, men and woman with reasoning of situation and condition of which different each other, not aside from student FBS Unesa. This purpose of research is description kinds of words pisuhan applied by students FBS Unesa according to gender, both context description of usage of word pisuhan student FBS IJnesa. This research is useful to develop theory in linguistics, pragmatic, and discourse analysis, practically is useful to know description kinds of words pisuhan and contexts of usage of wordses pisuhan in communicationses. This research menggunkan qualitative research method with analytical descriptive approach. Data source in the form ofwords in conversation of student FBS Unesa. Interview is done at 15 student informan people FBS Unesa dividend of 8 joe and 7 women. Data collecting done with observation method correct reading log, recorded, and in-depth interview.Data analytical technique applied by linguistic analytical method from Sudaryanto solid with qualitative data analysis adoption from Miles and Huberman. First research result, said pisuhan which usualy said by gender very men dominant said, that is; jancuk, dancuk, cuk, gathel, and there is also joined becoming cukgatheli. While pisuhan which applied by is woman most don’t differing from men. But that way some women in using word pisuhan there is diplesetkan for refining intonation. Said pisuhan said by dominant is woman for example that is ancrit (ancuk), methane (your eye), jancik (jancuk), brengkes (brengsek), bajigur (criminal), jambu, asem, keat (taek). Usage of word pisuhan which diplesetkan by group of woman the core important applied by student coming from culture mataraman. Second, context of usage of words pisuhan in student culture FBS Unesa is a) discourse field (field) word pisuhan emergence in easy going and also formal communications, b) Pelibat discourse (tenor) usage of word pisuhan is some of students FBS Unesa. c) Supporting facilities for discourse (mode) usage of word pisuhan student FBS Unesa that is verbally, in the form of monologue, and